2003
DOI: 10.1111/j.1572-0241.2003.07458.x
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Lactoferrin Is A Sensitive and Specific Marker in Identifying Intestinal Inflammation

Abstract: Fecal lactoferrin is sensitive and specific for detecting inflammation in chronic IBD. This noninvasive test may prove useful in screening for inflammation in patients presenting with abdominal pain and diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
193
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(206 citation statements)
references
References 13 publications
6
193
0
7
Order By: Relevance
“…21,22 Interestingly, stool lactoferrin has been shown to be a sensitive marker of intestinal inflammation in patients with intestinal tract symptoms and is being used in clinical practice to identify patients with intestinal tract inflammation. 23 Our results suggest that the detection of lactoferrin protein levels in the stool might also be a practical noninvasive screening test for pancreatic inflammation or cancer invasion among patients with suspected pancreatic disease. However, since stool lactoferrin is a feature of many other luminal gastrointestinal diseases, stool lactoferrin measurement may be too nonspecific for diagnostic use, even among patients with suspected pancreatic disease.…”
Section: Discussionmentioning
confidence: 69%
“…21,22 Interestingly, stool lactoferrin has been shown to be a sensitive marker of intestinal inflammation in patients with intestinal tract symptoms and is being used in clinical practice to identify patients with intestinal tract inflammation. 23 Our results suggest that the detection of lactoferrin protein levels in the stool might also be a practical noninvasive screening test for pancreatic inflammation or cancer invasion among patients with suspected pancreatic disease. However, since stool lactoferrin is a feature of many other luminal gastrointestinal diseases, stool lactoferrin measurement may be too nonspecific for diagnostic use, even among patients with suspected pancreatic disease.…”
Section: Discussionmentioning
confidence: 69%
“…[49][50][51][52] However, most studies found no difference in the faecal levels of calprotectin and lactoferrin between IBS patients and healthy controls. 43,44,49,50,[52][53][54][55][56][57][58][59] Only one publication reported that increased levels of faecal calprotectin were correlated with pain severity; however, this result was observed in children displaying both functional abdominal pain and IBS. 60 Key point: (i) Typically, no changes in the levels of the faecal inflammatory markers calprotectin and lactoferrin are reported in IBS patients.…”
Section: Key Pointsmentioning
confidence: 99%
“…In the present study we confirm the significant increase in lactoferrin but not calprotectin in stool samples. The patients and RT in the two studies are comparable, thus an explanation might be the relatively modest inflammation during RT, compared to the more extensive and pronounced inflammation present in inflammatory bowel diseases, where the two proteins are recognized as markers of intestinal inflammation [36,37].…”
Section: Inflammatory Markersmentioning
confidence: 99%